Maladaptive Modulations of NLRP3 Inflammasome and Cardioprotective Pathways Are Involved in Diet-Induced Exacerbation of Myocardial Ischemia/Reperfusion Injury in Mice. (14th December 2015) - Mastrocola, Raffaella; Collino, Massimo; Penna, Claudia; Nigro, Debora; Chiazza, Fausto; Fracasso, Veronica; Tullio, Francesca; Alloatti, Giuseppe; Pagliaro, Pasquale; Aragno, Manuela
Abstract : Excessive fatty acids and sugars intake is known to affect the development of cardiovascular diseases, including myocardial infarction. However, the underlying mechanisms are ill defined. Here we investigated the balance between prosurvival and detrimental pathways within the heart of C57Bl/6 male mice fed a standard diet (SD) or a high-fat high-fructose diet (HFHF) for 12 weeks and exposed to cardiac ex vivo ischemia/reperfusion (IR) injury. Dietary manipulation evokes a maladaptive response in heart mice, as demonstrated by the shift of myosin heavy chain isoform content from α to β, the increased expression of the Nlrp3 inflammasome and markers of oxidative metabolism, and the downregulation of the hypoxia inducible factor- (HIF-)2 α and members of the Reperfusion Injury Salvage Kinases (RISK) pathway. When exposed to IR, HFHF mice hearts showed greater infarct size and lactic dehydrogenase release in comparison with SD mice. These effects were associated with an exacerbated overexpression of Nlrp3 inflammasome, resulting in marked caspase-1 activation and a compromised activation of the cardioprotective RISK/HIF-2 α pathways. The common mechanisms of damage here reported lead to a better understanding of the cross-talk among prosurvival and detrimental pathways leading to the development of cardiovascular disorders associated with metabolic diseases.